TouchSense Glove / Muhammad Amir Azim Mohd Yuszaidi … [et al.] - Mohd Yuszaidi, Muhammad Amir Azim; Rahmat, Muhammad Daniel Afifi; Nor Azman, Muhammad Aiman Haris; Muhammad Saiful Iskandar, Jauza Imani; Mohd Khairul Anuar, Muhammed Daniel; Azis, Siti Noraziana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
TouchSense Braille Glove is a ground-breaking invention which developed especially to improve the freedom and sensory experience of blind people. This glove represents a revolution in how blind people engage with printed material because it uses cutting-edge technology to decipher Braille text through vibrating waves. The gloves have sophisticated sensors and microprocessors enable it to instantaneously convert typed text into vibrating patterns. Users may now feel and read Braille characters right from their fingertips.